Která formule je ta pravá? (Kritéria adekvátnosti logické analýzy) - Peregrin, Jaroslav; Svoboda, Vladimír (Organon F, 2012)
Transforming natural language sentences into formulas of a formal language (such as that of classical predicate logic) is a common practice that underlies most applications of logic to analysis of our reasoning/argumentation. Is this practice guided by any well established criteria? We argue that the answer is negative. The way from natural language to a formal one is much more tricky and much more arduous than it prima facie seems. We sketch a roadmap of this way and strive to explicate the criteria of adequacy of logical formalization that are implicit to the relevant practices. These considerations lead us to conceive logic as a project based on a search for a reflective equilibrium. Any formal system deserving the name logic must reach a balance between the authority of logical laws over individual arguments and their answerability to intuitive correctness of the bulk of such arguments.
Keywords: argument; logic; logical form; reflective equilibrium